A Reverse Transcription-Polymerase Spiral Reaction (RT-PSR)-Based Rapid Coxsackievirus A16 Detection Method and Its Application in the Clinical Diagnosis of Hand, Foot, and Mouth Disease - He, Shiyu; Huang, Yanzhi; Zhao, Yanling; Pang, Bo; Wang, Lixue; Sun, Liwei; Yu, Haoyan; Wang, Juan; Li, Juan; Song, Xiuling; Li, Hui (Frontiers in Microbiology, 2020)
Hand, foot and mouth disease (HFMD) is a common viral illness affecting infants and children that is usually caused by Coxsackievirus A16 (CVA-16). To diagnose HFMD, we developed a method for rapid detection of CVA-16 based on reverse transcription-polymerase spiral reaction (RT-PSR). We used two pairs of primers specifically recognize the conserved sequences of VP1 coding region of CVA-16, and template RNA was reverse transcribed and amplified in a single tube under isothermal conditions. Total reaction time could be reduced to less than 40 min. The detection limit of this method was between 2.4×102 and 2.4×101 copies/µL with excellent specificity. To test the clinical applicability of the method, 40 clinical stool samples were analyzed using RT-PSR and quantitative reverse transcription-polymerase chain reaction, and comparison showed that the coincidence rate was 100%. Compared with other similar detection methods, RT-PSR requires less time, simpler operation and lower cost. These results prove that our novel, simple and reliable isothermal nucleic acid testing assay has potential application for clinical detection of CVA-16.